Lymphoepithelioma-like carcinoma of the skin - Cristiano Claudino Oliveira; Vinicius Cardoso Nóbrega; Mariângela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Primary cutaneous lymphoepithelioma-like carcinoma is a rare disease with low metastatic potential. Its morphologic and pathological features are similar to those of nasopharyngeal lymphoepithelial carcinoma. We report the case of a 60-year-old man with an infrapalpebral pearly papule, measuring 0.6 cm in diameter. The lesion was excised with a clinical hypothesis of basal cell carcinoma or squamous cell carcinoma. Histopathological analysis revealed a malignant neoplasm with syncytial arrangement of cells with vesicular nuclei, associated with dense lymphocytic infiltrate. Immunohistochemistry revealed cytokeratin-positive cells (AE1/AE3) and p63 protein, indicating epithelial histogenesis and squamous differentiation. A negative Epstein-Barr virus test result was achieved by immunohistochemistry. Primary lymphoepithelioma-like carcinoma of the skin is a differential diagnosis of lesions with prominent inflammatory infiltrates.